HAWC and Fermi-LAT detection of extended emission from the unidentified source 2HWC J2006+341 - Albert, Andrea (2020)
The discovery of the TeV point source 2HWC J2006+341 was reported in the second HAWC gamma-ray catalog. We present a follow-up study of this source here. The TeV emission is best described by an extended source with a soft spectrum. At GeV energies, an extended source is significantly detected in Fermi-LAT data. The matching locations, sizes, and spectra suggest that both gamma-ray detections correspond to the same source. Different scenarios for the origin of the emission are considered and we rule out an association to the pulsar PSR J2004+3429 due to extreme energetics required, if located at a distance of 10.8 kpc.